Database-backed library web sites: a case study of the use of PHP and MySQL at the University of Nottingham - Gardner, Mike; Pinfield, Stephen (ASLIB, 2001)
This paper discusses the advantages of database-backed websites and describes the model for a library website implemented at the University of Nottingham using open source software, PHP and MySQL. As websites continue to grow in size and complexity it becomes increasingly important to introduce automation to help manage them. It is suggested that a database-backed website offers many advantages over one built from static HTML pages. These include a consistency of style and content, the ability to present different views of the same data, devolved editing and enhanced security. The University of Nottingham Library Services website is described and issues surrounding its design, technological implementation and management are explored.